Intercultural Perspectives on Research Writing, Pilar Mur-Dueñas, Jolanta Šinkūnienė, eds. John Benjamins, Amsterdam/Philadelphia (2018) - Varga, Mirna (Kalbotyra, 2019)
Intercultural Perspectives on Research Writing, Pilar Mur-Dueñas, Jolanta Šinkūnienė, eds. John Benjamins, Amsterdam/Philadelphia (2018). VII + 310 pp., ISBN 9789027201973.